Effect of a hypnosis session before hysterectomy on pre‐ and postoperative anxiety. Issue 1 (7th July 2021) - Sourzac, Jennie; Germain, Christine; Frison, Eric; Sztark, Francois; Conri, Vanessa; Floccia, Marie
Synopsis: A hypnosis session performed a few days prior to onco‐gynecological surgery can significantly reduce perioperative anxiety and postoperative pain.